ANALYSIS OF METHODS FOR COMPENSATION OF DIFFERENCES OF INTER-AXIAL DISTANCE IN A CONE TRANSMISSION - Sh.A. SHOOBIDOV; V.I. KOVALEVSKY; U.M. MAMASOBIROV (International Journal of Innovations in Engineering Research and Technology, 2021)
The article reviewed analysis of methods for compensating deviations of the axle distance in a bevel gear. A comparative assessment of methods for achieving the accuracy of the center distance in a traditional and fully adjustable bevel gear is presented. As a result of the analysis, it was concluded that it is advisable to directly regulate the interaxal distance in spur bevel gears of the compensating link in the form of a pair of rotary oblique washers.